2022
DOI: 10.1159/000521633
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Candida</i></b> Administration Worsens Neutrophil Extracellular Traps in Renal Ischemia Reperfusion Injury Mice: An Impact of Gut Fungi on Acute Kidney Injury

Abstract: Because of gut-barrier defect (gut-leakage) after acute kidney injury (AKI) and higher abundance of <i>Candida albicans</i> in human intestines compared with mouse guts, <i>Candida</i> administration in renal ischemia reperfusion injury (I/R) mice possibly more closely resemble patients with AKI than non-<i>Candida</i> model. Fungi in feces were detectable only in mice with <i>Candida</i> administration. <i>Candida</i> renal-I/R mice, when compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Studies have reported that the activation of neutrophil surface receptors such as NOX, Toll-like receptors (TLRs), Fc gamma receptor (FcγR), macrophage-1 antigen (Mac-1), programmed death ligand 1 (PD-L1), S1PR2 and dectin-1 may be involved in the initiation of NETosis, which involves the release of ROS (both NOX-derived and mitochondria-derived) or the elevation of intracellular calcium concentrations ( 59 62 ) ( Figure 1 ). ROS-related upstream signaling pathways, including protein kinase C (PKC), Raf/MEK/ERK, P38 mitogen-activated protein kinase (MAPK), Src/Syk, and PI3k/Akt, may medicate the NETosis induced by PMA, immobilized immune complexes, microbes, and diphenyl phosphate (DPHP) ( 51 , 63 66 ).…”
Section: Mechanisms Underlying the Formation Of Neutrophil Extracellu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that the activation of neutrophil surface receptors such as NOX, Toll-like receptors (TLRs), Fc gamma receptor (FcγR), macrophage-1 antigen (Mac-1), programmed death ligand 1 (PD-L1), S1PR2 and dectin-1 may be involved in the initiation of NETosis, which involves the release of ROS (both NOX-derived and mitochondria-derived) or the elevation of intracellular calcium concentrations ( 59 62 ) ( Figure 1 ). ROS-related upstream signaling pathways, including protein kinase C (PKC), Raf/MEK/ERK, P38 mitogen-activated protein kinase (MAPK), Src/Syk, and PI3k/Akt, may medicate the NETosis induced by PMA, immobilized immune complexes, microbes, and diphenyl phosphate (DPHP) ( 51 , 63 66 ).…”
Section: Mechanisms Underlying the Formation Of Neutrophil Extracellu...mentioning
confidence: 99%
“…Meanwhiles, in vitro , the activation of P2RX1 promoted platelet ATP release, which subsequently promoted the glycolytic metabolism of neutrophils and NET formation ( 105 ). In addition, the oral administration of Candida albicans to mice prior to renal I/R increased systemic inflammation and NETs through the activation of TLR-4 and dectin-1, exacerbating renal IRI ( 62 ). In line with these findings, Complement C3 KO mice with renal I/R showed attenuated renal injury when neutrophil infiltration and NET formation were reduced ( 106 ).…”
Section: Extracellular Traps In Organ Ischemia Reperfusion Injurymentioning
confidence: 99%
“…The synergy or additive effect of BG presentation upon LPS responses is intensively demonstrated through the activation of several innate immune cells (neutrophils, macrophages, and dendritic cells) [5,17,30,[54][55][56][57][58][59][60][61], possibly with the crosslink between TLR-4 and Dectin-1, the pattern recognition receptors (PRRs) for LPS and BG, respectively [62]. The similar downstream signaling through the NF-κB transcription factor of TLR-4 and Dectin-1 in these immune cells may be another explanation of the LPS-BG additive impact on several organs through the activation of immune cells (especially macrophages) inside these organs.…”
Section: The Additive Inflammatory Effect Of Lps Plus Bg a Key Pro-in...mentioning
confidence: 99%
“…Then, fungi in the gut can alter bacterial compositions in the gut and contribute to leaky gut-induced systemic inflammation in uremia through glucanemia and endotoxemia ( 22 ) and the abundance of gut organisms might be correlated with the level of pathogen molecules in blood during uremia-induced leaky gut ( 23 ). Due to the difference in the abundance of fungi in rodents versus humans, Candida administration might make the models more resemble humans ( 19 , 24 26 ). Indeed, the abundance of Candida spp.…”
Section: Introductionmentioning
confidence: 99%